نقوش عربية شمالية "ثمودية" من جبة - منطقة حائل / المملكة العربية السعودية - الشرمان، زياد مصطفى سعد (جامعة حسيبة بن بو علي الشلف - مخبر تعليمية اللغات وتحليل الخطاب, 2024)
يقدم هذا البحث دراسة تحليلية لغوية لمجموعة من النقوش العربية الشمالية (الثمودية)، التي عثر عليها في جبة بمنطقة حائل/ شمال غرب المملكة العربية السعودية. تهدف هذه الدراسة إلى إلقاء الضوء على هذه النقوش الجديدة، التي كتبت على الصخور، والتي تعرض سطح بعضها للتشويه؛ بسبب العوامل الجوية، أو بسبب كتابات ورسومات أكثر حداثة أضيفت عليها، نتج عن ذلك صعوبة قراءتها وعدم وضوح بعض أحرفها. نقلت هذه النقوش ونقحرت إلى العربية الفصحى، ودرست الأسماء والألفاظ الواردة فيها، وحللت تحليلا لغويا وافيا، وقورنت مع النقوش السامية الأخرى. تكمن أهمية هذا البحث في نشر النقوش الواردة فيه للمرة الأولى، كما أنها تفيد الباحث اللغوي الذي يريد التعرف على اللهجات العربية قبل الإسلام، والوقوف على لغة الثموديين ودراسة الأسماء والألفاظ الوردة فيها. This research presents a linguistic analytical study of a group of Northern Arabic (Thamudic) inscriptions, which were found in Jubbah in Ḥail region/ northwest of the Kingdom of Saudi Arabia. This study aims to shed light on these new inscriptions, which were written on rocks, the surface of some of which was subject to distortion; due to weather factors, or because of more recent writings and drawings added to it, this resulted in it being difficult to read and some of their letters being unclear. These inscriptions were transferred and transliterated into classical Arabic, and the names and words contained in them were studied thoroughly, linguistically analyzed, and compared with other Semitic inscriptions. The importance of this research lies in publishing the inscriptions contained therein for the first time. It also benefits the linguists who want to learn about pre-Islamic Arabic dialects, learn about the language of the Thamudeans, and study the names and words used in it.
Keywords: النقوش العربية -- الكتابة الثمودية -- الآثار السعودية